Long Term Impact of COVID-19 Infection on Sleep and Mental Health - Inayatullah Awan, Amjad Hussain Balouch, Anoop Kumar Juseja, Mukhtiar Ali Lakho, Abrar Shaikh, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the factors associated with contagious gastroenteritis in adults. Study design: Prospective study Place and duration of study: Department of Gastroenterology, New Life Hospital, Fateh Jang from 1st April 2021 to 30th September 2021. Methodology: Fifty patients, who were suspected of suffering from contagious gastroenteritis, were isolated in the private care setting until the confirmation of such through laboratory testing, faecal sampling/examination and scoring method, were enrolled. A well standardized questionnaire was generated for documenting all the demographic as well as clinical, examined history of patients with their faecal sampled results. Additional information about travel history, at least two months before gastroenteritis development, any infectious contact, recent antibiotic usage was also recorded. Results: There were more females as 81.8% in C. difficile cases and 48.71% in other contagious patients with gastroenteritis in comparison with 27.2% and 48.71% respectively. The age pattern showed that contagious gastroenteritis due to C. difficile was common in 25-45 years group, while 46-65 year age group was common for other contagious gastroenteritis. Around 45.45% patients with C. difficile and 51.2% other cases has a close contact with other people before admission. Also, there were 36.36% C. difficile cases with 1-2 month antibiotic usage history and 12.82% those cases of other contagious gastroenteritis with recent antibiotic usage. Conclusion: Contagious gastroenteritis is associated with factors such as age, travelling, antibiotic usage and mucous generation.